Somatic NLRP3 mosaicism in patients with “mutation-negative” CAPS: insights from a single centre UK cohort - Melo Gomes, Sonia; Arostegui, Juan I.; Mensa-Vilaro, Ana; Omoyinmi, Ebun; Hong, Ying; McCreary, Dara; Rowczenio, Dorota; Hawkins, Philip; Brogan, Paul (Frontiers in Pediatrics, 2025)
IntroductionKnowledge about mosaicism in cryopyrin-associated periodic syndromes (CAPS) has expanded significantly with the use of next generation sequencing technologies. The aim of this study was to assess the contribution of mosaicism in a paediatric cohort of patients with a clinical diagnosis of CAPS and no NLRP3 mutations identified through conventional DNA sequencing.MethodsMosaicism was assessed by amplicon-based deep sequencing (ADS) on DNA extracted from different tissues overtime. Targeted gene panels (TGPs) and whole-exome sequencing (WES) were used for comparison of detection methods.ResultsIn 40% (4/10) of the cohort a post-zygotic NLRP3 mutation leading to somatic mosaicism was found by ADS. Three of the detected NLRP3 mutations had been previously described only in somatic form and one both as germline and somatic. Mean mutant allelic frequencies (MAF) at diagnosis varied between 3.1-14.5% in whole blood, with all mutations being present in other tissues tested. In 3 patients, mosaicism was evaluated over time in whole blood, with results confirming mosaicism stability in 2 patients, and a MAF increase in 1 patient (from 1.9% to 5%). TGPs identified 4/4 cases of mosaicism whilst WES detected only 1/3.DiscussionSomatic NLRP3 mosaicism was present in 40% of this paediatric cohort, confirming the key role of this phenomenon in disease pathogenesis and in genetic confirmation of CAPS diagnosis. MAFs can be extremely low, which warrants caution regarding lower detection limits of the sequencing techniques utilized. Mosaicism level may vary over time in some patients, with diagnostic and potential therapeutic implications.